TEACHER’S CHANGES AND CHALLENGES IN CLIL IMPLEMENTATION - Hien, Tran Thi Thu (VNU Journal of Foreign Studies; Vol 38 No 6DO - 10.25073/2525-2445/vnufs.4883, 2022)
This study aims at finding out high school English teachers’ changes and challenges in content and language integrated learning in Vietnam. Survey questionnaires and in-depth interviews have been chosen to collect data for the study. The results show that teachers have made encouraging changes in lesson planning, material development, lesson delivery and assessment. The challenges encountered by the teachers involve the subject knowledge, teachers’ time and effort allowances, learners’ motivation and supporting policies. The results of the study can be considered an informative source of reference for future CLIL implementation at schools across our country.